A kind of energy-efficiency wireless sensor network model based on passive clustering algorithm. (5th January 2015) - Zhou, Jing; Wang, Jingshi
This paper presents an energy-efficiency wireless sensor network (WSN) model; the model based on passive clustering strategy creates its clustering network topology only when there are data communication requests in WSN, and the creation and the maintenance of the topology are both local to complete, and need no extra control commands to save energy. In this clustering strategy, the selection of cluster head takes a mechanism named 'first declarant enunciator wins'. The election of gateway node is decided according to the rules that make trade-offs between the network robust and energy-efficient. The creation and maintenance process of the cluster network are described in detail in this paper. The simulation result is also presented in NS2, which shows that directed diffusion routing that adopts the model is more energy-efficient than those that do not adopt it, and has a good performance even when the nodes number increases in large scale.